Mathematicians in pre-war national defense forces of Lithuania - Algirdas Ažubalis (Lietuvos Matematikos Rinkinys)
The article presents condensed biographical data and activity analysis on the 15 Lithuanian mathematicians who served in pre-war National Defense Forces of Lithuania, with the special emphasis on their contribution to strengthening national defense potential of the country.